ANALYSIS OF ELECTROMECHANICAL COUPLING DYNAMIC CHARACTERISTICS OF SERVO DRIVE SYSTEM - LI WenLi; LIU YongKang; GUO Dong; LU Yu; SHI XiaoHui; ZHENG WeiDong (Jixie qiangdu)
In order to explore the influence of the changes of electromagnetic parameters and mechanical parameters on the dynamic characteristics of servo drive system,based on the relevant theories of mechanical dynamics and electromagnetism,builded a four-inertia electromechanical coupling model including motor electromagnetic stiffness and electromagnetic damping.Obtained the time history curve,phase plane diagram,Poincare mapping and amplitude-frequency characteristic curve of the system by using 4～5 order Runge-Kutta method with variable step size. Analyzed effects of the changes of electromagnetic stiffness,excitation frequency and transmission comprehensive error on the motion state of the electromechanical coupling system.Under different electromagnetic stiffness values,the system will change from period doubling bifurcation to period 1 motion,and then to chaotic motion,and when the electromagnetic stiffness decreases from 5 × 10~5 Nm/rad to 10~5 Nm/rad,the maximum amplitude of the system will increase by 7%. The change of mechanical parameters such as gear meshing error will change the motion state of the system,and when the fluctuation coefficient of comprehensive transmission error increases from 0. 05 to 0. 2,the amplitude of the system will increase by 16%.